How do Economic Reforms affect the Structure of Wages? The Case of Brazilian Manufacturing, 1984-1996 - Jorge Saba Arbache (University of Kent, Department of Economics, 1998)
One of the established findings in the literature on inter-industry wage differentials is the long-term stability of the wage structure. In this paper, we examine how market-oriented and other economic reforms undertaken by an industrialising country affect the dispersion and structure of wages. Using a large, individual-level dataset, we find that the labour market is highly responsive to the economic reforms undertaken in Brazil in the early 1990s. Wage dispersion falls dramatically just after the implementation of economic reforms and we find evidence that the wage structure is under transition after the changes. Human capital variables gain importance in the explanation of wage differentials, while industry affiliation and institutional characteristics become less important. This finding is consistent with the labour market being flexible enough to adapt to the new economic conditions, and becoming more competitive as a result of the economic reforms.
Keywords: J31; 330; Economic reforms; wage structure; wage dispersion; Brazil; Wirtschaftsreform; Sektorale Lohnstruktur; Brasilien